The Effect Of Lemon Aromatherapy On Emesis Gravidarum In Pregnant Women In The First Trimester At The Singosari Public Health Center - Devi Muninggar; Raden Maria Veronika Widiatrilupi (Universitas Prima Indonesia, 2026)
One of the most common discomforts experienced in the first trimester is nausea and vomiting or emesis gravidarum. This condition generally occurs due to increased levels of the hormones human chorionic gonadotropin (hCG), estrogen, and progesterone which affect the gastrointestinal system and the vomiting center in the brain. The purpose of this study was to determine the Effect of Lemon Aroma Therapy on Emesis Gravidarum at the Singosari Malang Community Health Center. The research design was a Pre Experiment with one group pretest posttest with control group research. The population in this study were all pregnant women at the Singosari Community Health Center who were pregnant in the first trimester. The sample in this study was 20 pregnant women in the first trimester of pregnancy aged 1-12 weeks using purposive sampling. Data analysis used univariate and bivariate analysis using the Chi square test. The results of the study showed a Chi square test (p value = 0.000). The conclusion of this study shows that there is an Effect of Lemon Aroma Therapy on Emesis Gravidarum at the Singosari Malang Community Health Center. It is recommended that pregnant women gain additional knowledge about Lemon Aroma Therapy for Emesis Gravidarum by seeking information from both print and electronic media.